2012
DOI: 10.5194/isprsarchives-xxxviii-4-w25-87-2011
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Stage Approach to Travel-Mode Segmentation and Classification of GPS Traces

Abstract: ABSTRACT:This paper presents a multi-stage approach toward the robust classification of travel-modes from GPS traces. Due to the fact that GPS traces are often composed of more than one travel-mode, they are segmented to find sub-traces characterized as an individual travel-mode. This is conducted by finding individual movement segments by identifying stops. In the first stage of classification three main travel-mode classes are identified: pedestrian, bicycle, and motorized vehicles; this is achieved based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…The reference lists of excluded reviews were reviewed and potential papers were gathered. Finally, 12 published papers matching all the criteria were included in this review [1,31,[38][39][40][41][42][43][44][45][46][47], as shown in Table 2. In particular, we selected [39] because the segment identification method of this study is a significant data preprocessing technique for travel mode detection.…”
Section: Systematic Review Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The reference lists of excluded reviews were reviewed and potential papers were gathered. Finally, 12 published papers matching all the criteria were included in this review [1,31,[38][39][40][41][42][43][44][45][46][47], as shown in Table 2. In particular, we selected [39] because the segment identification method of this study is a significant data preprocessing technique for travel mode detection.…”
Section: Systematic Review Processmentioning
confidence: 99%
“…Zhang et al [44] calculated the values of speed and heading from point positions and time stamps and utilized a smoothing method to reduce speed errors by averaging the neighborhood.…”
Section: Data Preprocessing Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…These limitations increase the difficulty in extracting health‐related activity information from smartphone‐measured GPS traces. Current protocols of GPS data processing were primarily designed for transportation mode detection (Gonzalez et al , Zheng et al , Zhang et al , Gong et al ), travel behavior analyses (Wolf et al , Auld et al , Papinski et al , Schüssler and Axhausen , Clark and Doherty , Oliver et al , Millward and Spinney , Millward et al ), and movement analyses (Ashbrook and Starner , Vazquez‐Prokopec et al ). A common practice of these protocols is to divide the sequence of GPS points into segments based on similarities of point characteristics such as speed and acceleration.…”
Section: Introductionmentioning
confidence: 99%